Association between exposure to sedentary behavior and dietary, social and mental health factors in adolescents from the state public network of Sergipe (Research, Society and Development, 2021)
The aim of the study was to investigate an association between exposure to sedentary behavior (ECS) with bullying, low consumption of fruits and vegetables and consumption of soda in adolescent schoolchildren from public schools in the State of Sergipe. The study stands out for being cross-sectional based, with a representative sample of 4139 adolescents between 14 and 19 years old. Data were obtained using the Global Student Health Survey questionnaire (GSHS, WHO). The dependent variable was presented to sedentary behavior (ECS), so adolescents who spent more than 4 hours a day in sedentary activities were considered sedentary. The independent variables were: negative perception of stress, bullying, feeling of loneliness and difficulty sleeping due to worry, low consumption of fruits plus vegetables and soft drinks. Binary logistic regression analysis was used to associate the variables. In adolescents, the variables feeling of loneliness, stress and soft drink consumption were associated with ECS. In boys, only as psychosocial variables, feeling of loneliness and stress associated with the outcome. The known that adolescents' ECS is associated with the feeling of loneliness and stress and consumption of soda, and with these results it is evident that there is a need to reduce physical inactivity and the consumption of unhealthy foods.